2016
DOI: 10.1016/j.prosdent.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A technique for assessing the fit of a removable partial denture framework on the patient and on the definitive cast

Abstract: Figure 2. A, Inject low viscosity polyvinyl siloxane material on tissue surface and place intraorally. B, Evaluate thickness of impression material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Silicone film method is commonly performed by inserting silicone impression material between the RPD and intraoral dentition or master model under a retentive force that is maintained through the setting time. The the silicone replica of the gap may be sectioned afterwards and its thickness directly revealing the gap was measured with stereomicroscope, digital microscope, electronic calipers or profile projector [ 18 , 35 , 45 , 46 ]. However, Yoon et al reported that the number of measuring points have effect on the average thickness of the silicon replicas, and that the accuracy of silicone film method was not sufficiently reliable [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicone film method is commonly performed by inserting silicone impression material between the RPD and intraoral dentition or master model under a retentive force that is maintained through the setting time. The the silicone replica of the gap may be sectioned afterwards and its thickness directly revealing the gap was measured with stereomicroscope, digital microscope, electronic calipers or profile projector [ 18 , 35 , 45 , 46 ]. However, Yoon et al reported that the number of measuring points have effect on the average thickness of the silicon replicas, and that the accuracy of silicone film method was not sufficiently reliable [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the low overall internal discrepancy value is not equivalent to better fit, as it is the compounded result of individual components. The RPD rests could be the ideal reference for the fit evaluation, which is easy for measurement and important for functional loading of the overall framework [ 45 ]. The fit accuracy of other RPD components, namely the connectors, the clasp arms as well as denture base should be further investigated for both digital and conventional fabrication technologies.…”
Section: Discussionmentioning
confidence: 99%
“…After setting of the PVS, the frameworks with the registration material were removed and excess materials were trimmed and a light body rubber base impression material was injected on the fitting surface of the PVS material and immediately placed in the patient mouth ensuring that all the components were in their position intraorally. After setting of the impression material, the frameworks were removed from the mouth and careful measurements of the thickness of the impression materials at different locations were performed by a single examiner [16]. The resulted measurements were statistically analyzed using the two-tailed t-tests.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Accurate master casts are fundamental to the successful rehabilitation of partially edentulous patients with removable partial denture (RPD) prostheses. One of the greatest challenges in the treatment of partially dentate patients is lack of fit of the RPDs [1]. Such RPD's will usually fit the master cast but not intraorally; this is an indication that the master cast may have been poured from an inaccurate impression.…”
Section: Introductionmentioning
confidence: 99%